Visualizing water molecules in transmembrane proteins using radiolytic labeling methods - Orban, Tivadar (2010)
Essential to cells and their organelles, water is both shuttled to where it is needed and trapped within cellular compartments and structures. Moreover, ordered waters within protein structures often co-localize with strategically placed polar or charged groups critical for protein function. Yet it is unclear if these ordered water molecules provide structural stabilization, mediate conformational changes in signaling, neutralize charged residues, or carry out a combination of all these functions. Structures of many integral membrane proteins, including G protein-coupled receptors (GPCRs), reveal the presence of ordered water molecules that may act like prosthetic groups in a manner quite unlike bulk water. Identification of ‘ordered’ waters within a crystalline protein structure requires sufficient occupancy of water to enable its detection in the protein's X-ray diffraction pattern and thus the observed waters likely represent a subset of tightly-bound functional waters. In this review, we highlight recent studies that suggest the structures of ordered waters within GPCRs are as conserved (and thus as important) as conserved side chains. In addition, methods of radiolysis, coupled to structural mass spectrometry (protein footprinting), reveal dynamic changes in water structure that mediate transmembrane signaling. The idea of water as a prosthetic group mediating chemical reaction dynamics is not new in fields such as catalysis. However, the concept of water as a mediator of conformational dynamics in signaling is just emerging, owing to advances in both crystallographic structure determination and new methods of protein footprinting. Although oil and water do not mix, understanding the roles of water is essential to understanding the function of membrane proteins.